DARWINISME SOSIAL DAN KEAMANAN INTERNASIONAL: SEBUAH ANALISIS RINGKAS - Ariesani Hermawanto (Jurnal Paradigma, 2019)
The development of socio-biology science brings changes to the security of humansocial life. The biological theory about evolution made discussion that was identified as Social Darwinism. This thought was based on assumptions that human life through natural selection and always in conflict by competition to fight for life, keep the existence, and also survival of the fittest. Social Darwinism in its history produced ideology like Fascism and has made tragedies in the eras of World Wars I and II. As a thought, Social Darwinism still continues today.The competition between countries in the new Millennium era, both in the arms race and economic competition, are reflection of Darwinist thougt.